(untitled) (Research, Society and Development, 2021)
In this paper, we analyze the consumption habits and perceptions of Brazilians and Americans regarding the consumption, preparation and handling of the coffee product and its packaging, in order to better think about translating the packaging of coffee produced in southern Minas Gerais to the USA market. Through bibliographic research and other resources, information such as preparation, reasons for consumption, and place of consumption were compared between the two populations to understand if there were relevant cultural differences. The packaging of eight coffee brands, four from each country, was also compared in order to notice any differences and similarities between them. The results show that there are indeed differences between the two cultures, both in their habits and in their packaging. Some examples are the valorization of the semantic field of coffee in Brazilian packaging, and the preference for quick methods of brewing the product for the Americans. We conclude that any translation of Brazilian coffee for the American public must consider these differences. Finally, we present some possibilities for packaging translation, using for this the idea of country brand and its influences on consumers, as well as the concepts of Localization, Intersemiotic Translation and Paratranslation.